2020
DOI: 10.1182/blood-2020-140682
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Outcomes of Patients of Middle Eastern Ethnic Origin with Autologous Haemopoietic Stem Cell Transplantation and COVID-19: Does a Dampened Immune System Protect Against Severe COVID-19?

Abstract: Introduction Outcomes of patients with hematological cancers and coronavirus disease 2019 (COVID-19) have been reported to be poor with high rates of hospitalization, mechanical ventilation with high case fatality rates, mortality being around 10% or higher. The mortality had been particularly higher among blacks and ethnic minority individuals. There is paucity of data on the outcomes of patients with autologous stem cell transplant and concurrent COVID-19 infections, especially from eastern me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Selected studies reported retrospective observational data from single‐centre experiences [4– 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], multicentre experiences [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] or registry data [ 7 , 8 , 42 , 43 , 44 , 45 ]. Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies [ 8 , 15 , 18 , 19 , 23 , 24 , 29 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 41 , 44 , 45 ] were from Europe (1153 patients), seven studies [ 4 , 6 , 17 , 20 , 22 , 25 , 36 ] were from North America (238 patients), seven studies [ 5 , 16 , 21 , 26 , 30 , 32 , 42 ] were from the Middle East (185 patients), two studies [ 28 , 40 ] were from South America (41 patients), one study [ 27 ] was from Asia (28 patients) and two studies [ 7 , 43 ] included patients from multiple regions (496 patients). Seventeen studies [ 7 , 8 , 16 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 35 , 38 , 39 , 40 , 41 , 45 ] included both adult and paediatric transplant recipients, 13 studies […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations